Pelatihan Dan Simulasi Mitigasi Bencana Longsor Berbasis Masyarakat Di Desa Dermasuci Kecamatan Pangkah Kabupaten Tegal - Anisa Oktiawati; Ita Nur Itsna; Risnanto Risnanto (UNIVERSITAS BHAMADA SLAWI, 2020)
Law No. 24 of 2007 concerning Disaster Management by the Government of Indonesia on April 26, 2007, has brought a new dimension in disaster management in Indonesia. Disaster management has become a preventive activity, so that disaster can be prevented or minimized (mitigation) so that the risk can be reduced. Indonesia is one of the countries that are very vulnerable to disasters. Government policies are needed to reduce the risk of disasters such as disaster mitigation. Landslides that occurred in Dermasuci Village occurred due to the accumulation of high rainfall. A land movement occurred 3 years ago in the north of the current disaster site and resulted in 6 housing being damaged. The aim of community service is that the community is expected to be able to increase awareness of environmental sustainability, life safety, and the potential hazards of landslides in the surrounding areas. The target of this activity is all levels of society in Dermasuci Village. The results are namely the success of the target number of trainees can be judged good, given the target number of trainees of 35 people, meanwhile in the implementation of training activities both the first and second days that can be present as many as 30 people (85%). The limited-time provided means that not all subjects can be delivered in detail. Many of them were only delivered in a broad outline, so it is very possible that participants with different educational backgrounds still lack understanding of the knowledge provided by the service team.